2019
DOI: 10.1136/ijgc-2019-000310
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of differential ascites volume with primary cytoreductive surgery outcome, lymph node involvement, and disease recurrence in advanced ovarian cancer

Abstract: ObjectiveHigh-grade serous ovarian cancer accounts for a disproportionate number of deaths from gynecologic malignancies. It typically presents at an advanced stage and with a high volume of ascites a common presenting feature. The aims of this study is to evaluate the association between ascites volume at the time of primary surgery for advanced stage ovarian cancer with surgical outcomes and patterns of recurrence.MethodsA retrospective review of stage III/IV high-grade serous ovarian cancer patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(10 reference statements)
0
4
0
Order By: Relevance
“… 7 Ascites could be an independent prognostic indicator, considering that more than 90% of ovarian cancer patients with malignant ascites are diagnosed with stage III and IV cancer. 8 , 9 Immune cells and cytokines are important components of malignant ascites and are associated with disease progression. 6 Previous studies have shown that the immunoreactive phenotype is consistent with lower ascites volume.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Ascites could be an independent prognostic indicator, considering that more than 90% of ovarian cancer patients with malignant ascites are diagnosed with stage III and IV cancer. 8 , 9 Immune cells and cytokines are important components of malignant ascites and are associated with disease progression. 6 Previous studies have shown that the immunoreactive phenotype is consistent with lower ascites volume.…”
Section: Introductionmentioning
confidence: 99%
“…More than one‐third of ovarian cancer patients developed ascites at initial diagnosis and ascites is likely to further cause chemoresistance, widespread metastasis, and decreased surgical resectability 19–22 . A recent study showed that HGSC patients with ascites <200 mL have lower serum CA125 levels, more optimal cytoreduction rates, and longer disease‐free intervals than those with large ascites 23 . However, most ascites research focuses on HGSC, and determining the importance of ascites in the progression of rare EOC subtypes, such as OCCC, is currently difficult.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 , 22 A recent study showed that HGSC patients with ascites <200 mL have lower serum CA125 levels, more optimal cytoreduction rates, and longer disease‐free intervals than those with large ascites. 23 However, most ascites research focuses on HGSC, and determining the importance of ascites in the progression of rare EOC subtypes, such as OCCC, is currently difficult. The present study revealed that survival analysis showed ascites (>400 mL) as an independent OS‐ and PFS‐related factors for patients with OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were defined as optimally cytoreduced as ≤1cm of residual disease. Malign high-volume ascites were described as serous fluid (>200 mL) in the peritoneal cavity (7). Lymphovascular Space Invasion (LVSI) was diagnosed when endothelial-lined spaces with or without intraluminal red cells or lymphocytes were observed in tumor tissue.…”
Section: Patientsmentioning
confidence: 99%